The Impact of Demographic Change on Economic Growth in ASEAN - BOUARAXAY, Vanhnasone; SOMSAMONE, Vilayphone; DUANGPASITH, Phatsa (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
To study the impact of Demographic Change on Economic Growth in ASEAN. This study uses panel data from 1993 to 2022 from ASEAN countries by collecting data from the World Development Indicator, World Bank 2023, consisting of GDP per capita, working age population, Youth dependency population, and Elderly dependency population. We utilize the statistical completion program as a tool to help with the Panel Autoregressive Distributed Lag Approach (ARDL) method analysis. The results of the study found that variables are stationary at I(0) and I(1) level. Moreover, the estimated coefficients of the variables with the Pooled Mean Group reveals that Working age population had a positive impact in long-run on the GDP per capita in ASEAN countries, Youth dependency population had a negative impact in long-run on the GDP per capita in ASEAN countries, and also had a speed of adjustment to long-run equilibrium and for Elderly dependency population were not statistically significant. The result of Mean Group and Dynamic Fixed Effect further shows that there were not statistically significant. By means of the Hausman test, the results can be concluded that Pooled Mean Group estimation is most suitable.